The health status of students in the USSR in the 1920’s - Khoruzhenko, Khrystyna (Skhid, 2014)
The article is dedicated to the issues of physical, infectious and mental health of Ukrainian students in the 1920-th years, and analyzes the factors that directly make worse this condition. Separately we explore issues of power to prevent sexually transmitted epidemics, epidemics of typhoid, tuberculosis and other diseases. We also study such factors that have caused students’ diseases as housing insecurity, lack of funds for the existence and complete lack of moral prohibitions- because of a radical change in the value of personality after the revolution and the civil war.